Fictive Layering and Inversion in the Paintings of Ali-Akbar Sadeghi. Issue 4 (3rd July 2016) - Foroutan, Aida
Abstract : In Iran surrealism is spoken of by artists and critics as a living element in art, long after its popularity in Europe and North America has waned. This article explores key features of the work of one of the most prolific contemporary Iranian artists, Ali-Akbar Sadeghi. While Sadeghi says that he thinks of himself as a "surrealist, " his work is distinguished from many self-professed surrealists in Iran: whereas the latter are concerned with representing metaphysical, even mystical, meanings, Sadeghi sees his art as a kind of intellectual exercise, presenting a dramatic theater in which the viewer engages in epistemological interrogation. Though Sadeghi's paintings are full of apparent references to surrealist themes and tropes from the past, here it is argued that his work is not so much a storehouse of surrealist content as a series of puzzles for the viewer to solve.